2019
DOI: 10.3390/electronics8020153
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Virtual Experiments for Microwave Imaging of Complex Scenarios

Abstract: In this paper, a multiresolution approach for the quantitative microwave imaging of complex scenarios is introduced. The proposed strategy takes advantage of the combined use of a recently introduced iterative method known as distorted iterated virtual experiments (DIVE), based on the paradigm of “virtual experiments”, and a wavelet-based projection scheme. This strategy allows the unknown profiles to be represented at different resolution scales and, as such, it is particularly suitable for the imaging of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Some other studies as shown in Table A2 focussed on the algorithms and methodologies employed for breast cancer detection, rather than on the hardware apparatus. This table summarizes the most recent innovative and effective methodologies for breast cancer imaging [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. Those methodologies aimed at achieving multi-resolution images.…”
Section: Radar-based Microwave Imagingmentioning
confidence: 99%
“…Some other studies as shown in Table A2 focussed on the algorithms and methodologies employed for breast cancer detection, rather than on the hardware apparatus. This table summarizes the most recent innovative and effective methodologies for breast cancer imaging [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. Those methodologies aimed at achieving multi-resolution images.…”
Section: Radar-based Microwave Imagingmentioning
confidence: 99%
“…In both cases, several prototypes have been proposed over the past decade [11][12][13][14][15][16][17], and some of them reached a high level of maturity, being tested on up to 400 women in pre-clinical stage [11]. Most recent works on microwave imaging have been published in 2019 and 2020 [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…While the goal of various quantitative microwave imaging techniques for GPR applications (including APEX and SPOT-GPR) is to detect, localize and characterize discrete buried objects, other approaches aim at an overall electromagnetic reconstruction of the underground structures, and more specifically at a qualitative or quantitative estimation of the geometrical distribution of the physical properties of media (dielectric permittivity, electric conductivity) in the subsurface [35,36]. Such methods are promising for the analysis of radargrams obtained in highly heterogeneous environments [37]. Sparse reconstruction algorithms find application in the imaging of targets embedded in stratified dielectric media [38,39].…”
Section: Introductionmentioning
confidence: 99%